Perencanaan Pondasi Tiang Pancang pada Hotel 5 Lantai di Magelang (Indonesian Journal of Civil Engineering Study, 2025)
Magelang City, as a prominent tourist destination frequently visited by both domestic and international travelers, requires adequate facilities and infrastructure to support visitor accommodation. This study focuses on the foundation design of a five-story hotel in Magelang Regency, where pile foundations were selected as the structural system. Precast concrete piles were manufactured in factories and transported to the project site for installation. The research employed both qualitative and quantitative approaches, including literature review, expert interviews, and analysis of completed project cases. The calculation results indicate that the reinforcement requirements are 25,747.4 kg for Type 1 pile foundations and 44,342.4 kg for Type 2 pile foundations, with a total of 70,089.8 kg. Type 1 foundations measure 3.6 m × 3.6 m × 0.8 m with a depth of 1 m, while Type 2 foundations measure 3.6 m × 5.4 m × 0.8 m with the same depth. Future research is recommended to investigate the dynamic response of pile caps and piles under seismic loads.
Keywords: Dynamic Response; Pile Foundation; Planning; Precast Concrete; Structural System